2018
DOI: 10.1002/ccr3.1643
|View full text |Cite
|
Sign up to set email alerts
|

Median arcuate ligament syndrome and aneurysm in the pancreaticoduodenal artery detected by retroperitoneal hemorrhage: A case report

Abstract: Key Clinical MassageHere, we report a case with successful treatment of inferior pancreaticoduodenal artery aneurysm rupture due to celiac artery trunk compression caused by the median arcuate ligament. When clinicians see visceral aneurysms, the possibility of arcuate midline ligament compression syndrome (MALS) and ligamentectomy for MALS should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…This suggests that awaiting catheter intervention or one-staged procedure in the hybrid operating room is necessary unless intraoperative verification of CA flow using a Doppler flow meter is available. 10 ) We used the transit-time flow meter to confirm SMA blood flow because there was no probe suitable for the size of CA. Measuring the antegrade flow in one of the CA branches would have been useful to detect residual stenosis in the CA.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that awaiting catheter intervention or one-staged procedure in the hybrid operating room is necessary unless intraoperative verification of CA flow using a Doppler flow meter is available. 10 ) We used the transit-time flow meter to confirm SMA blood flow because there was no probe suitable for the size of CA. Measuring the antegrade flow in one of the CA branches would have been useful to detect residual stenosis in the CA.…”
Section: Discussionmentioning
confidence: 99%
“…Sanchez et al reported a case of MALS with liver ischemia that improved with conservative follow-up [ 5 ]; the other reported cases of MALS underwent reoperation using a MAL incision [ 3 , 6 ]. In non-acute-onset MALS, surgical MAL incision would be more desirable than endovascular treatment with IVR or arterial bypass [ 2 ], because re-laparotomic procedures after PD would be difficult because of adhesions and effects on the reconstructed organs. Imai et al performed IVR prior to MAL incision, but they eventually performed a second surgery because of CA re-occlusion, which resulted in a third surgery, remnant pancreatectomy, and splenectomy [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because median arcuate ligament (MAL) syndrome (MALS), also called “celiac axis compression syndrome” [ 1 , 2 ], may be fatal if left untreated at the time of pancreaticoduodenectomy (PD) [ 3 , 4 ], it is diagnosed preoperatively and treated with preoperative interventional radiology (IVR) or intraoperative surgical treatment. However, MALS can also occur postoperatively, even if the diagnosis of MALS is not based on preoperative or intraoperative evaluation [ 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Median arcuate ligament syndrome (MALS) is a rare disease that results from extraluminal compression of the coeliac artery by the median arcuate ligament of the diaphragm[ 1 ]. MALS occurs in 2 per 100000 patients[ 1 - 3 ]. Typical clinical findings include postprandial abdominal pain, upper abdominal murmur, and weight loss.…”
Section: Introductionmentioning
confidence: 99%